What Do 32 COVID-19 Deployments of Emergency Medical Teams Tell Us about Challenges and Lessons Learned? - Ramnath Vadi (22457662) (2025)
The COVID-19 pandemic showed the vital role of Emergency Medical Teams (EMTs) in international surge responses. The EMTs with their internationally skilled team members were able to meaningfully support countries facing the pandemic, especially those who were suffering from scarcity in the quality and quantity of workforce and financial resources within their health systems. This report summarizes the main operational challenges faced by UK-Med and The Polish Center for International Aid (PCPM) Emergency Medical Teams, based on experiences from their 32 COVID-19 deployments. In particular, the paper discusses the hindrances related to Ministries of Health expectations and the changing roles of EMTs during deployments. Other Information Published in: Disaster Medicine and Public Health Preparedness License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1017/dmp.2025.70